Implementation of Sexual Education to Prevent Promiscuity - Wardani, Amallia Putri Kusuma; Ramadani, Fazrineka; Rahmadani, Fitria; Rahmah, Sintya Ayu; Shobabiya, Mahasri (EDUCTUM: Journal Research, 2023)
The purpose of this research is to prevent promiscuity through the implementation of sexual education, and to develop the character of Muslims with piety and noble morals. This research uses library research by collecting information and data using different types of materials such as documents, articles, past journals, etc. The application of sexual education is very important today because this study found that Indonesian teenagers are having extramarital sexual relationships that go against religion and norms. In this study, it is important to remember that sex education is knowledge that enables children to recognize the functions of their own bodies. Additionally, young people are made aware of the ethical and social rules that apply and the consequences of their actions. Because without sex education, they will become curious about taking risks in the development of their sexual orientation, which will have fatal consequences in preventing promiscuity.